Assessment of drug content uniformity of atropine sulfate triturate by liquid chromatography–tandem mass spectrometry, X-ray powder diffraction, and Raman chemical imaging. Issue 1 (December 2016) - Moriyama, Kei; Takami, Yoichiro; Uozumi, Natsuki; Okuda, Akiko; Yamashita, Mayumi; Yokomizo, Rie; Shimada, Kenichi; Egawa, Takashi; Kamei, Takehito; Takayanagi, Kazunobu
Abstract Background Atropine sulfate is an anticholinergic agent for treatment of hypertrophic pyloric stenosis and is orally administrated as a triturate with lactose hydrate. Because of the low safety margin of atropine sulfate, triturate uniformity is a key safety factor. In this study, we assessed the uniformity of atropine sulfate in 1000-fold triturates prepared by wet mixing and dry mixing methods and discussed the cause of the difference in uniformity between two preparation methods. Methods A 1000-fold triturate of atropine sulfate with lactose hydrate was prepared by two different methods: wet mixing and dry mixing. The wet mixing was performed according to Kurashiki Central Hospital protocol and the dry mixing was a simple physical mixing by a rocking mixer. The uniformity of atropine sulfate content in aliquots of a 1000-fold triturate with lactate hydrate was assessed by liquid chromatography–tandem mass spectrometry (LC–MS/MS) quantification. Solid-state analyses of the triturates by Raman chemical imaging and X-ray powder diffraction (XRPD) were performed to investigate the difference in uniformity. Results The LC–MS/MS quantification showed that the uniformity of atropine sulfate in the 1000-fold triturate was excellent for wet mixing but was significantly variable for dry mixing. On the basis of the Raman chemical imaging and XRPD analyses, it was indicated that an amorphous thin film of atropine sulfate coated the surfaces of the lactose hydrate particles during wet mixing and contributed to the uniformity of the triturate. In contrast, clusters of the crystalline atropine sulfate were found in the dry mixing samples. Conclusion The results showed that better atropine sulfate triturate uniformity was achieved using the wet mixing method rather than the dry method and the cause of the uniformity difference between two mixing methods was indicated by the multilateral assessment.